Evaluation of screening for drug use using postmortem prolactin levels in serum and cerebrospinal fluid. (November 2019) - Tani, N; Ikeda, T; Aoki, Y; Shida, A; Oritani, S; Ishikawa, T
Prolactin (PRL) levels can usually be controlled by PRL-inhibiting psychiatric drugs that include anti-dopamine agents. However, the use of dopamine (DA) antagonists may lead to hyperprolactinemia under certain clinical conditions. The aim of this study was to investigate postmortem PRL levels as potential markers of drug abuse, especially that of DA antagonists, in autopsy cases. We examined 121 autopsy cases, excluding cases involving acute hypoxia/ischemia, such as asphyxia, because PRL concentrations are reportedly increased under acute hypoxic conditions. Detected drugs were classified as either DA antagonists, stimulants, psychotropic drugs other than DA antagonists, or other non-psychotropic drugs, and many cases had no detected drugs. Samples comprised blood collected from the right heart chamber and cerebrospinal fluid (CSF). PRL protein level was measured by chemiluminescent immunoassay, and PRL gene expression in the anterior pituitary of autopsy cases was analyzed by reverse transcription-polymerase chain reaction. The PRL-positive cell ratio in the anterior pituitary gland was also measured by immunohistochemical analysis. The results indicated that PRL levels in the serum and CSF were higher in DA antagonist cases than in other cases. PRL levels in the serum and CSF also correlated with the PRL gene expression in cases with abuse of DA antagonists. However, no significant difference in the PRL-positive cell ratio in the anterior pituitary gland was evident between any of the classes of drug-detected and drug-undetected cases. These results suggest that postmortem measurements of PRL transcription levels may be useful for diagnosing cases of DA antagonist use.